Produção heteróloga de inibidores de pectina metil esterase (PMEI), para ensaios de inibição com PME e Invertase, enzimas intestinais do Sphenophorus levis - Araque, Camilo Orozco (Universidade Federal de São Carlos, 2018)
The pectin is a fundamental part of the cell wall from plants and it is composed mainly by 4 polysaccharides. The polysaccharide most abundant is the homogalacturonan (HG) representing up to 65% from pectin, and it is a homopolymer of galacturonic acid, mainly methyl esterified. The HG is a substrate for pectin remodeling enzymes, also called pectinases. The pectinase that participates in the first phase of pectin degradation is the Pectin Methylesterase (PME) (E.C.3.1.1.1.1). This enzyme catalyzes the hydrolysis of two groups methyl ester of the principal chain of HG. In previous works of our laboratory we identified and characterized a PME (Sl-PME) in a cDNA library of the sugarcane weevil, Sphenhophorus levis. The PMEs from plants can be inhibited by endogenous inhibitors from plants, the Pectin Methylesterase Inhibitors (PMEIs). The inhibition is achieved by the formation of a pH dependent 1.1 complex. Until now there is no report of an inhibition the insects PMEs by plants PMEIs, which was tested in this work. On the other our laboratory also identified an S. levis invertase, called Sl-invertase. The Sl-invertase has digestive function and hidrolise the sacarore. Structurally PMEIs share high identity with invertase inhibitors (INH). That inhibitors comprise a large plant protein family known as PMEI-related proteins (PMEI-RP). Therefore we also decide to investigate the inhibition of Sl-invertase by PMEIs. Inhibitors from four species of plants: Actinidia deliciosa (Kiwi), Saccharum hybrid (Sugar cane), Solanum lycopersicum (Tomato) e Vitis americana (Grape) were cloned and recombinantly produced in the yeast Pichia pastoris. The Sl-PME and Sl-invertase were also were expressed in the yeast P. pastoris. Neither the inhibitors inhibited the Sl-PME activity, although a complex of Sl-PME and sugarcane PMEI was identified in vitro. Regarding the Sl-invertase it was significantly inhibited by the PMEIs from tomato (20%) and sugar cane (40%).
Keywords: Pectina Metil Esterase (PME); Sphenophorus levis; Inibidores de Pectina Metil Esterase (PMEIs); Pectinases; Herbivoria; Invertase; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR